International medical knowledge transfer as a tool of public diplomacy : the case of Croatia - Daraboš, Nikica (Array, 2020)
The international dissemination of expertise in most transition countries is underdeveloped because of a number of developmental and practical challenges. Croatia’s overall educational and innovatory potential for health knowledge transfer remains above average when compared to what has been achieved by other new EU Member States, and it is dominated by public sector research institutes and universities. This unrealized potential could be improved further by enhancing the international dissemination of Croatian medical expertise using public diplomacy. The aim of this paper is to address the way in which the international dissemination of medical expertise in transition countries can serve as a tool of public diplomacy to improve its scope and success, in addition to advancing the scope of the knowledge transfer itself. The case of Croatia is used as an example. An effective communication strategy is an important element of public diplomacy that, by influencing public opinion, provides the necessary precondition for active societal support of the willing participants in the transfer of knowledge. Hence, at the beginning of this paper we present the concept of international knowledge transfer in general, and then proceed to present the example of the transfer of Croatian medical knowledge. The second part of this paper addresses elements of public diplomacy and different communication mechanisms and the potential for the international dissemination of domestic medical expertise, with the primary emphasis on Croatia. Finally, we present an overall analysis and an algorithm of public diplomacy activities that each country in transition can adopt to overcome failures associated with the international dissemination of medical expertise.